2021
DOI: 10.3390/app11094156
|View full text |Cite
|
Sign up to set email alerts
|

Sizing and Sitting of DERs in Active Distribution Networks Incorporating Load Prevailing Uncertainties Using Probabilistic Approaches

Abstract: In this study, a microgrid scheme encompassing photovoltaic panels, an energy storage system, and a diesel generator as a backup supply source is designed, and the optimal placement for installation is suggested. The main purpose of this microgrid is to meet the intrinsic demand without being supplied by the upstream network. Thus, the main objective in the design of the microgrid is to minimize the operational cost of microgrid’s sources subject to satisfy the loads by these sources. Therefore, the considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The maximum value of each power block is enforced by (3). The real power of DGs is constrained by the minimum and maximum output of DGs as in (4). For ESSs, the charging and discharging power limits of ESSs are enforced by ( 5) and ( 6).…”
Section: Centralized Energy Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum value of each power block is enforced by (3). The real power of DGs is constrained by the minimum and maximum output of DGs as in (4). For ESSs, the charging and discharging power limits of ESSs are enforced by ( 5) and ( 6).…”
Section: Centralized Energy Managementmentioning
confidence: 99%
“…In addition, a microgrid could facilitate the secure and efficient operation of the utility grid by providing operational supports in many aspects, e.g., frequency and voltage regulation, virtual inertia, etc. [1][2][3][4]. As a unique virtue, a microgrid could seamlessly transit from grid-connected to islanding operation and continue to supply its local customers independently [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The output current of the PV cells can be modelled following the next equation: [11] 𝐼 = 𝐼 𝑝ℎ − 𝐼 0 (𝑒…”
Section: System Under Considerationmentioning
confidence: 99%
“…Also, they can produce a high torque output compared to doublyfed induction generators caused by the density and the high magnetic flux efficiency. [11][12][13] The battery is connected to the DC bus side via DC bidirectional converter, which can ensure the storage operations. The battery control depends to different traditional like PI and hysteresis regulators, their comportment is more discussed in [14,15], it is very simple and based on generation of high amplitude oscillations which had a nice effect on the quality and performance of the considered system [14,15], the authors in [15] present the advantages of the linear PI regulator for battery current regulation, it has simple implementation, and in the opposite, it hasn't a high stability under quick variation of weather conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Nematollahi et al in [5], addressed the problem of microgrids distributed generations optimal sizing and sitting with the objectives to minimize the resources generation cost and mitigate power losses. In this context, it has been proposed to use the lightning attachment procedure optimization It has been shown that this procedure outperforms the artificial bee colony approach in terms of convergence speed and the accuracy of solution-finding.…”
Section: Special Issue Contributionsmentioning
confidence: 99%